Conversational Korean everyday phrases and vocabulary : ideal for K-pop and K-drama fans - The Calling
"This super-cute, full-colour phrasebook covers all the situations you are likely to encounter in daily life, whether at school, work, hanging out with your friends, discussing your favourite K-Pop bands, having computer problems, meeting the love of your life or suffering from a broken heart. Frequent cultural notes give useful guidelines on a wide variety of topics including how to use formal and informal language and tips for visiting popular tourist destinations such as Seoul, Busan and Jeju. You'll also find nuggets of useful information on topics ranging from best Korean food and traditional alcohol to the symbolism of dreams in Korean culture! The unique features of this phrase book are that it includes a much wider range of situations than the usual phrasebook and the phrases reflect the kind of language you actually use! For example, as well as basic greetings, transport, and restaurants, there are sections on plastic surgery, beards and moustaches, smoking, and jealousy and betrayal."--Publisher's description.